The Impact of Nutritional Status on Gastrointestinal Symptoms, Hyperactivity Disorders, and Sleep Problems in Children with Autism Spectrum Disorder - Fatma Özsel Özcan Araç; Irem Özcan (Proceedings)
Autism spectrum disorder is a neurodevelopmental disorder that presents with repetitive behavior and weakness in social interaction. The nutritional problems experienced by children with autism aggravate the symptoms of autism, but also cause aggravation of the gastrointestinal system, an increase in hyperactivity disorders and sleep problems. This study was conducted to measure the effects of the nutritional status of children with autism on GIS symptoms, hyperactivity disorders and sleep problems. This study was conducted to measure the effects of the nutritional status of children with autism on GIS symptoms, hyperactivity disorders and sleep problems. The study was carried out with the families of children with autism at Kartal Umut Işığı Special Education and Rehabilitation Center. Within the scope of the study, a questionnaire consisting of four parts was given to the parents of 62 children with autism. The questionnaire included a voluntary consent form, personal information form, Conners Parent Rating Scale (CADS-48) and food frequency questionnaire. The parents completed these questionnaires in a face-to-face environment. The data obtained from the questionnaires were analyzed and presented with the SPSS 22 program. As a result of the study, it was found that different food groups can affect GI problems, hyperactivity disorders and sleep problems. It was found that the children who consumed dry broad beans did not have GIS complaints, and the children who consumed fast food experienced the problem of hyperactivity more regularly (p < 0.05). It was concluded that children who did not have GIS problems did not have sleep problems (p < 0.05). It was confirmed that simple carbohydrate consumption causes hyperactivity in children, but no significant results were found regarding GI problems and sleep disorders in the literature, and there are studies that overlap or contradict our study. More work is needed on this subject.